KAMPUNG INVESTASI HATI SERVICE FACILITY AS A SOLUTION-ORIENTED APPROACH TO MENTAL HEALTH PROBLEMS IN THE COMMUNITY; MONOGRAPH ANALYSIS - Ni Ketut Sri Diniari; Luh Nyoman Alit Aryani; Marianto, Marianto; Michael Surya; Merryanggy Saiba; Angela Azalia Trisna Putri (International Journal of Social Science, 2025)
Background: Mental disorders represent a complex public health issue that requires a comprehensive rehabilitative approach. In Indonesia, the increasing prevalence of people with mental disorders highlights the need for rehabilitation services that integrate medical, social, and psychological components. Objective: This study aims to analyze the rehabilitation needs of individuals with mental disorders at the Kampung Investasi Hati Service Facility as a strategic approach to addressing mental health problems in the community. Methods: A descriptive cross-sectional design was employed using total sampling of all residents and Kampung Investasi Hati Service Facility staff. The “Pulih Questionnaire” was used to assess clinical symptoms and social functioning. Data were obtained through interviews, observation, and document review, and were analyzed descriptively using frequency distribution and narrative synthesis. Results: The majority of residents were male, aged >60 years, diagnosed with hebephrenic or paranoid schizophrenia, and had stayed for more than five years. Basic needs were fulfilled; however, psychosocial rehabilitation remained minimal. Daily activities did not follow the established schedule, and only a few residents participated in vocational therapy. Several facilities required improvement, including bedrooms, toilets, activity rooms, and security systems. Human resources were limited; most staff were non-medical personnel and lacked continuous mental health training. Variation in treatment centers created challenges in monitoring therapy. Mean clinical symptom scores (6.41%) approached the threshold for clinical attention, while social functioning scores were within the moderate category (13.48%). Conclusion: Rehabilitation needs at the Kampung Investasi Hati Service Facility have not been optimally met. Strengthening human resources, improving infrastructure, establishing structured rehabilitation programs, and enhancing coordination with healthcare facilities are required to ensure continuity of care.